Novel Cell Culture Paradigm Prolongs Mouse Corneal Epithelial Cell Proliferative Activity in vitro and in vivo - An, Xiaoya; Wang, Guoliang; Jin, Mengyi; Zhou, Xiaoping; Gao, Shubin; Chen, Jingyao; Reinach, Peter S.; Liu, Zuguo; Xue, Yuhua; Li, Cheng (Frontiers in Cell and Developmental Biology, 2021)
It has been a long-standing challenge to obtain from cell cultures adequate amounts of mouse corneal epithelial cells (mCEC) to perform transplantation surgery. This limitation is attributable to the passage dependent declines in their proliferative activity. We describe here development of a novel 6C medium that contains six different modulators of different signaling pathways, which control proliferative mCEC activity. Its usage shortens the time and effort required to obtain epithelial sheets for hastening healing of an epithelial wound in an experimental animal model. This serum-free 6C medium contains:Y27632, forskolin, SB431542, DAPT, IWP-2, LDN-193189 and also DermaLife K keratinocyte calcium. Their inclusion inhibits rises in four specific markers of epithelial mesenchymal transdifferentiation:ZEB1/2, Snail, β-catenin and α-SMA. This medium is applied in a feeder-free air-lifted system to obtain sufficient populations of epithelial progenitor cells whose procurement is facilitated due to suppression of progenitor epithelial cell transdifferentiation into epithelial-mesenchymal cells. Diminution of this decline in transdifferentiation was confirmed based on the invariance of P63, K14, Pax6, and K12 gene expression levels. This cell culture technique is expected to facilitate ex vivo characterization of mechanisms underlying cell fate determination. Furthermore, its implementation will improve yields of progenitor mouse corneal epithelial cells, which increases the likelihood of using these cells as a source to generate epithelial sheets for performing transplantation surgery to treat limbal stem cell deficiency in a clinical setting. In addition, the novel insight obtainable from such studies is expected to improve the outcomes of corneal regenerative medicine.